Right, Not Reward: A Doctrinal Boundary for Managerial Tools in Zakat Governance - Andriyani Andriyani; Arnaz Agung Andrarasmara; Eko Aryani; Afina Hasya (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This conceptual study examines the doctrinal limits of managerial practices in zakat governance by distinguishing managerial tools that facilitate the delivery of divinely mandated rights from those that redefine eligibility for zakat recipients. It addresses the growing adoption of nonprofit management practices in Islamic social finance and their implications for Shariah compliance. Design/methodology/approach – The study employs an integrative conceptual approach by drawing on the Qur'an, Sunnah, classical juristic scholarship across the four Sunni schools, contemporary fatwas of the International Islamic Fiqh Academy and the Indonesian Council of Ulama, and an integrative-critical review of zakat governance literature indexed in Scopus, Web of Science, and DOAJ (2013–2025). Findings – The study classifies managerial practices into five categories: verification, administrative efficiency, needs-based sequencing, conditionality, and performance-based selection. It argues that only performance-based selection, in its strong form, conflicts with Shariah by transforming the fixed right of eligible beneficiaries into a reward for projected productivity. The findings further support severity-based prioritisation while rejecting productivity-based beneficiary selection and propose a governance framework consisting of six design principles and five testable propositions. Originality/value – This study provides a jurisprudential framework that reconciles managerial effectiveness with doctrinal fidelity by distinguishing permissible administrative innovations from practices that alter zakat entitlement. It offers a practical governance model for Islamic social finance institutions seeking to improve efficiency without compromising Shariah principles.